Combining Bacteriophage Lysin LYSGH15 and Celery (Apium graveolens L.) Apigenin for Treating Staphylococcus aureus Pneumonia in Children - Muhammad Habiburrahman; Stefanus Sutopo; Delly Chipta Lestari (PT Kalbe Farma Tbk., 2023)
Pneumonia is one of the devastating diseases that affect children under five and can result in high incidence and significant mortality rates. A substantial subset of these cases is caused by Staphylococcus aureus (S. aureus), a Gram-positive bacteria that can cause severe complications and even death. Additionally, antibiotic resistance complicates this problem further. In order to combat this issue, combining flavonoids and bacteriophage products may be a critical solution in decreasing morbidity and mortality rates of pneumonia. Apigenin, extracted from celery (Apium graveolens L.), which has anti-inflammatory and antioxidant effects. Combined with bacteriophage lysin, it can work synergistically against infections and inflammation without being easily resisted by bacteria. This literature review focuses on the use of apigenin and phage lysin, LysGH15, as a treatment for children’s pneumonia, sourced from Google Scholar and PubMed, using several combined keywords such as “new treatment”, “children pneumonia”, “Staphylococcus aureus”, “MRSA”, “new antibacterial”, and “therapy”. Combination therapy shows potential as a new treatment candidate for children’s pneumonia. Pneumonia dikenal sebagai salah satu penyakit paling mematikan pada anak di bawah 5 tahun, dengan insiden 156.000.000 kasus per tahun, dan angka kematian yang signifikan. Salah satu penyebab penting penyakit ini adalah bakteri Gram-positif Staphylococcus aureus (S. aureus), yang sering menyebabkan komplikasi dan kematian. Peningkatan resistensi S. aureus terhadap antibiotik juga memperumit kondisi ini. Kombinasi perawatan yang berasal dari produk flavonoid dan bakteriofag mungkin dapat menjadi kunci untuk menurunkan morbiditas dan mortalitas. Apigenin adalah salah satu jenis flavonoid yang dapat diekstrak dari seledri (Apium graveolans L.). Bersama dengan lisin dari bakteriofag, kedua komponen ini bekerja secara sinergis dalam kasus infeksi dan peradangan, dengan keunggulan berupa tidak mudah mengalami resistensi oleh bakteri. Tinjauan literatur berasal dari Google Scholar dan PubMed menggunakan beberapa kata kunci: “pengobatan baru”, “pneumonia anak”, “Staphylococcus aureus”, “MRSA”, “antibakteri baru”, dan “terapi” berfokus pada penggunaan apigenin dan lisin bakteriofag, LysGH15, sebagai pengobatan untuk pneumonia anak. Terapi kombinasi ini diharapkan berpotensi untuk dikembangkan sebagai pengobatan pneumonia anak.